Kadar Kolesterol Total Wanita Menopause Hiperkolesterolemia Sesudah Pemberian Teh Buah Tin - Muslimatul Akhfiya; Agustin Syamsianah; Mufnaetty . (Universitas Muhammadiyah Semarang, 2018)
Ficus Carica Fruits known as tin fruits contain high antioxidants which are believed to be able to help decreasing total cholesterol level. This study aimed to determine the difference in totalcholesterol levels of menopausal women with hypercholesterolemia before and after tea of ficus carica fruits treatment.This research was experimental study with pre-post test controlled groupdesign. Fourty menopausal women with total cholesterol >200 mg/dL were divided into 2 groups, the intervention group (P1; n=20) which was given two bags of tin tea (4 g); and the control group (P2; n=20) which was given the water considered as control. The samples were taken by the randomsampling method. Analysis of normality data using Kolmogorov-Smirnov test and continued with paired t-test statistic and independent t-test to determine the significant differences. Total cholesterol level of P1 significantly decreased by 119,45 mg/dl (p<0,01); while total cholesterollevel in control group decreased by 1,15 mg/dl (p=0,072). Giving the tea of ficus carica fruits can significantly decrease total cholesterol in menopausal women with hypercholesterolemia.Keywords: tin tea, hypercholesterolemia, menopausal women, total cholesterol level.